PERFORMANCE OF PADJADJARAN QUAILS GROWER PERIOD FEED WITH DIFFERENT ENERGY AND PROTEIN LEVELS - QUDDUS, MUHAMMAD FEBRYANTONO; Setiawan, Iwan; Sujana, Endang (Fakultas Peternakan, Universitas Padjadjaran, 2023)
This study aimed to determine the recommended energy and protein level of the Padjadjaran quail's broiler feed for a 3-6 weeks growth period on its production performance. The treatments applied were nine ratios with different energy and protein levels, consisting of P1=(ME 2800 kcal/kg, protein 20 %); P2=(ME 2800 kcal/kg, protein 22 %); P3=(ME 2800 kcal/kg, 24 % protein), P4=(ME 2900 kcal/kg, 20 % protein); P5=(ME 2900 kcal/kg, 22 % protein); P6=(ME 2900 kcal/kg, 24 % protein); P7=(ME 3000 kcal/kg, 20 % protein); P8=(ME 3000 kcal/kg, 22 % protein); P9=(ME 3000 kcal/kg, 24% protein). Each treatment was replicated three times, and each replicate consisted of four quails. The results of the data were processed using analysis of variance. The observed variables included ratio consumption, weight gain, FCR, carcass weight, and abdominal fat. The results showed that the protein energy level of the ratios was not significantly different (P>0.05) on ratio consumption, body weight gain, FCR, carcass weight, and abdominal fat. Differences in diet protein and energy levels did not significantly affect the performance of the Padjadjaran quail's broiler during the growth period. The recommended diet for the growth period is a feed containing EM 2900 kcal/kg and 20% protein, as it resulted in the highest body weight gain and carcass weight and more efficient feed intake.